Optical clearing of apple tissues for in vivo imaging of the pathogenic behavior of the fungus Botryosphaeria dothidea on host surfaces - Ki Woo Kim; Eun Woo Park (Applied Microscopy)
Abstract Optical clearing of apple tissues was performed to observe the pre-penetration behavior of Botryosphaeria dothidea. Mature red fruits and two-year-old twigs were artificially inoculated with the fungal conidia. Fruit epidermis and twig cork tissues were excised and immersed overnight in an ethanol-chloroform solution amended with trichloroacetic acid. Lactophenol cotton blue was used to stain the fungus on the host surfaces. The morphology and behavior of the inoculated B. dothidea could be clearly observed in the two types of optically cleared specimens. The conidia showed either monopolar or bipolar germination, leading to the emergence of germ tubes from one or both conidial ends. Conidia formed appressoria at the terminal ends of germ tubes. They appeared round, hook-shaped, and irregular-shaped in two-dimensional light micrographs. Multiple appressoria were observed on the suberized phellem cells in twig lenticels. These results suggest that the optical clearing technique and fungal staining were effective in partially decolorizing apple tissues and revealing the fungal structures on the host surfaces.